2015
DOI: 10.1088/2041-8205/807/1/l9
|View full text |Cite
|
Sign up to set email alerts
|

AN ULTRA-LUMINOUS QUASAR AT z = 5.363 WITH A TEN BILLION SOLAR MASS BLACK HOLE AND A METAL-RICH DLA AT z ∼ 5

Abstract: We report the discovery of an ultra-luminous quasar J030642.51+185315.8 (hereafter J0306+1853) at redshift 5.363, which hosts a supermassive black hole with = ´ M M (1.07 0.27) 10 , J0306+1853 is one of the most luminous objects in the early universe. It is not likely to be a beamed source based on its small flux variability, low radio loudness, and normal broad emission lines. In addition, a = z 4.986 damped Lyα system (DLA) with = -1.3 0.1, among the most metal-rich DLAs at  z 5, is detected in the absorp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 51 publications
(100 reference statements)
1
14
0
Order By: Relevance
“…If we also include less reliable M BH estimates (∆σ * > 20 km s −1 ), the range extends to log(M BH /M ) 10.3. Notwithstanding the uncertainties related to this latter high-mass end, we note that it is consistent with the highest masses seen in inactive SMBHs in the local Universe (e.g., McConnell et al 2011McConnell et al , 2012; the most massive SMBHs observed out to z ∼ 6 (e.g., Shemmer et al 2004;Wang et al 2015;Wu et al 2015) and perhaps the highest BH masses that could be observed as (radiatively efficient) accreting systems (Inayoshi & Haiman 2016;King 2016;Pacucci et al 2017). The Eddington ratios of our sources lie below the Eddington limit and in the range −2.2 log λ Edd −0.2, with a median log λ Edd = −1.3.…”
Section: Accretion Demographicssupporting
confidence: 83%
“…If we also include less reliable M BH estimates (∆σ * > 20 km s −1 ), the range extends to log(M BH /M ) 10.3. Notwithstanding the uncertainties related to this latter high-mass end, we note that it is consistent with the highest masses seen in inactive SMBHs in the local Universe (e.g., McConnell et al 2011McConnell et al , 2012; the most massive SMBHs observed out to z ∼ 6 (e.g., Shemmer et al 2004;Wang et al 2015;Wu et al 2015) and perhaps the highest BH masses that could be observed as (radiatively efficient) accreting systems (Inayoshi & Haiman 2016;King 2016;Pacucci et al 2017). The Eddington ratios of our sources lie below the Eddington limit and in the range −2.2 log λ Edd −0.2, with a median log λ Edd = −1.3.…”
Section: Accretion Demographicssupporting
confidence: 83%
“…Recently, large-area surveys for high-redshift quasars have identified a number of high-luminosity quasars with z>5 (Wang et al 2015(Wang et al , 2016Wu et al 2015). These quasars are detected in some of the dropout bands owing to their extreme brightness.…”
Section: Supplementary Quasar Selectionmentioning
confidence: 99%
“…Based on a Figure 1. BH masses of high-redshift quasars (star symbols, from left to right: ULASJ1120+0641 at z = 7.1, J0306+1853 at z = 5.4, and SDSSJ0100+2802 at z = 6.3) in comparison with other z > 6 quasars (small grey ellipse), and the area populated by a large number of lower-redshift SDSS quasars (large grey ellipse; adopted from Wang et al 2015).…”
Section: Triggering Of Quasar Activitymentioning
confidence: 99%